Masculinity in Gender Relations: Hegemonic Masculinity and Masculine Power Discourse in Turkey. (2nd January 2018) - Keskin, Fatih
Abstract : The erosion, or crisis, of modern democracies has long been an issue. One reason for this situation is the masculine structure of politics and governments, and their policies rendering women subordinate to men, which threaten the normative assumption that democracy is affected by the egalitarian structure of society and the gender regime, and similarly, the settlement of gender relations in society depends on a resistant democratic system. In fact, this article demonstrates that politics is culturally perceived as a man's occupation, and women's role in active politics is restricted to center-right and center-left parties. This trend is observably continuing today, bringing about masculine discourse and practices in the hegemonic approach to politics.